Survival and biomarker analysis for ovarian mucinous carcinoma according to invasive patterns: retrospective analysis and review literature - Taira Hada; Morikazu Miyamoto; Hiroki Ishibashi; Hiroko Matsuura; Takahiro Sakamoto; Soichiro Kakimoto; Hideki Iwahashi; Hitoshi Tsuda; Masashi Takano (BMC, 2021)
Abstract Background In ovarian mucinous carcinoma, invasive pattern is the important factor but there were less reposts to investigate it. The aim of this study was to examine the association between prognosis and invasive patterns of ovarian mucinous carcinoma and to investigate the biomarkers of the diagnosis and prognosis immunochemically. Patients with ovarian mucinous carcinoma at our institution between 1984 and 2018 were identified. A pathological review was conducted using the 2020 World Health Organization criteria. The prognosis of infiltrative invasion and expansile invasion of ovarian mucinous carcinoma were retrospectively compared. In addition, immunohistochemical staining was conducted for all cases, and the immunohistochemical differences between the two invasive patterns were compared. Results After the pathological review, 25 cases with infiltrative invasion and 24 cases with expansile invasion were included. Ovarian mucinous carcinoma with infiltrative invasion showed significantly worse progression-free survival (PFS, p < 0.01) and overall survival (OS, p < 0.01) than those with expansile invasion. Multivariate analysis demonstrated that the pattern of infiltrative invasion was a worse prognostic factor for PFS (hazard ratio 9.01, p < 0.01) and OS (hazard ratio 17.56, p < 0.01). Immunohistochemically, cytokeratin (CK) 5/6 (p = 0.01), cluster of differentiation (CD) 24 (p = 0.02), and epithelial growth factor receptor (EGFR) (p < 0.01) were statistically related to infiltrative invasion. The PFS (p = 0.04) and OS (p = 0.02) of cases with EGFR-positive OMC were worse than those with negative OMC. Conclusions Infiltrative invasion was observed to be a prognostic factor showing worse outcomes for ovarian mucinous carcinoma compared to expansile infiltration. CK5/6, CD24, and EGFR might be biomarkers of the diagnosis.